160k views
2 votes
Can someone help me out ? Don't just guess the answer :(

Can someone help me out ? Don't just guess the answer :(-example-1
User Vdclouis
by
6.2k points

2 Answers

2 votes
The first one will be equal to 1

The second one is 10x+19/ (x+4)(x-3)



User Freegnu
by
5.2k points
3 votes
1) 2m+6 / m² + 7m - 12 + (m+2)/(m+4)

= 2(m+3) / (m+4)(m+3) + (m+2)/(m+4)

= 2/(m+4) + (m+2)/(m+4)

= 2+m+2 / (m+4)

= m+4 / m+4

= 1 [ Option A ]

Answer 2) 3/ (x+4) + 7/ (x-3)

= 3(x-3) + 7(x+4)/ (x² +x - 12)

= 3x-9 + 7x + 28 / (x² +x - 12)

= 10x + 19 / (x² +x - 12) [ Option A ]

Hope this helps!
User Thomas Watson
by
6.5k points